PENGUATAN KESEHATAN MENTAL REMAJA MELALUI EDUKASI PENCEGAHAN KEKERASAN DAN BULLYING - Elisabeth Iswantiningsih; Siti Mahmudah; Endang Tri Sulistyowati; Hernawan Isnugroho (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2024)
Bullying and violence remain common problems among adolescents and have negative impacts on mental health. Low levels of knowledge and empathy regarding the consequences of bullying contribute to the persistence of such behavior. This community service activity aimed to improve adolescents’ knowledge and empathy related to the prevention of violence and bullying toward mental health through educational interventions. The method used was health education with promotive and preventive approaches, including interactive lectures, discussions, video presentations, and pre-test and post-test assessments. The participants were 40 adolescents aged 13–18 years. The results showed an increase in the average knowledge score from 56.8 in the pre-test to 82.5 in the post-test. In addition, the empathy score increased from a moderate category (61.2) to a high category (85.4). These findings indicate that the educational intervention was effective in improving adolescents’ understanding and concern about the impacts of bullying and the importance of prevention. This activity is expected to serve as a promotive and preventive effort to support adolescent mental health and to create a safe social environment free from violence and bullying.